Economic integration with unequal partners: the Caribbean and North America - Worrell, DeLisle ([s.n.] [S.l.], 1993)
Attempts to define the Caribbean and explores the ways in which the desire for regional association might be realised in terms of economic links. Looks at Caribbean achievements and failures and reviews efforts in the English-speaking Caribbean to set up regional political and economic structures that would help to achieve the common Caribbean identity. Discusses relationships between the English-speaking countries and the rest of the Caribbean, North America and Latin America. Describes how global changes have affected North American policies and attitudes toward the Caribbean. Looks at future prospects for Caribbean-North American integration.